Nuclear versus cytosolic activity of the yeast Hog1 MAP kinase in response to osmotic and tunicamycin‐induced ER stress. Issue 16 (30th June 2015) - García-Marqués, Sara; Randez-Gil, Francisca; Prieto, Jose A.
Abstract : We examined the physiological significance of the nuclear versus cytosolic localization of the MAPK Hog1p in the ability of yeast cells to cope with osmotic and ER (endoplasmic reticulum) stress. Our results indicate that nuclear import of Hog1p is not critical for osmoadaptation. Plasma membrane‐anchored Hog1p is still able to induce increased expression of GPD1 and glycerol accumulation. This is a key osmoregulatory event, although a small production of the osmolyte coupled with the nuclear import of Hog1p is sufficient to provide osmoresistance. On the contrary, the nuclear activity of Hog1p is dispensable for ER stress adaptation. Abstract : The nuclear import of Hog1p is not essential to face with hyperosmotic and ER stress. Accumulation of glycerol is a key osmoregulatory event. Glycerol production is mainly regulated by transcriptional induction of GPD1 . The Hog1 nuclear function becomes more relevant when the cells capacity to accumulate glycerol is impaired.